Genetic Diversity Among Some Promising Indian Local Selections and Hybrids of Cashew Nut Based on Morphometric and Molecular Markers. Issue 1 (2nd January 2016) - Jena, Ram C.; Samal, Kailash C.; Pal, Ajantaa; Das, Basant K.; Chand, Pradeep K.
ABSTRACT: The present investigation reports an elucidation of genetic diversity among 12 promising Indian cashew nut cultivars, including 9 local selections and 3 hybrids on the basis of morphometric and yield parameters as well as random amplified polymorphic DNA (RAPD) markers. Dice dissimilarity coefficient was used to discriminate cultivars with respect to gross phenotypic characters such as plant growth, flowering, fruit, and nut characters. DNA from these cultivars were subjected to polymerase chain reaction (PCR) using 35 decamer oligonucleotide primers of which 15 primers were able to generate informative polymorphism (average 79.187%). The unweighted pair group method using arithmetic average (UPGMA) dendrogram segregated the cashew cultivars into two main clusters at 0.53 Jaccard's similarity coefficient. Five different primers were identified with the ability to discriminate eight cultivars based on a unique band pattern. Although both morphometric descriptors and RAPD markers proved their effectiveness for distinguishing the different cultivars in cashew germplasm of India, the superiority of the latter was explicit being more informative as to genotypic discrimination and establishing genetic relationships.